HOME BUYING DECISIONS: INFLUENCE OF QUALITY, SERVICE, AND INCOME LEVEL (STUDY CASE ON GRIYA ARTHA RANCABANGO HOUSING DEVELOPER) - Kurniawan, Rocky Rinaldi; Yuliyzar, Ismayudin; Pratama, Putra; Kurniastuti, Cahyani (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
Property prices are getting higher and higher, making it difficult for people to buy them. One factor that determines the purchase of a property or house is the quality of its products, services, and the level of income of the surrounding community. This study aims to examine the effect of product quality, credit service, and community income levels on home purchase decisions in Griya Artha Rancabango, Tangerang. The research method used is descriptive associative research. The population and sample in this study are buyers and potential buyers of Griya Artha Rancabango. The results showed that it can be concluded that the quality of the product (X1 ) has a positive and significant influence on the purchasing decision (Y) of the house. That the service (X 2 ) has a positive and significant influence on the purchase decision (Y) of the house. That the level of consumer income (X 3 ) has a positive and significant influence on purchasing decisions (Y) houses. that the level of product quality (X1 ), service (X2 ), and consumer income (X3 ) have a positive and significant influence on purchasing decisions (Y) Griya Artha Rancabango.